The Expansion Dance of Alpha Centauri - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2021)
Using Alpha Centauri as an example, it will be investigated how two-mass systems rotating around their barycenter evolve with the age of the universe. It is calculated how change the masses, the periods, the distance and the gravitational value. As the universe ages, both mases fall, the gravitational value increases quadratically, all system periods increase, and the distance between the two objects increases with the periods. The eccentric dance of the two stars expands accordingly.